Creating Business Value through Flexible IT Architecture. - Helbig, Johannes; Scherdin, Alexander (Computer (00189162), 2007)
The article discusses the case of Deutsche Post World Net to illustrate the role of flexible information technology (IT) architecture in creating business value. Deutsche Post transformed its antiquated and inefficient IT structure by pursuing a gradual approach that balanced the needs of business value and IT integrity. The logical service architecture employed was decentralized, with responsibilities tied to specific business units. In the end Deutsche Post achieved both greater efficiency and a reduction in the increase of IT costs.